Presenting and investigating the efficacy of an educational interactive mobile application for British Sign Language using hand gesture detection techniques - Restituyo, Cristian A.; Loizides, Fernando; Yang, Shufan; Weir, Kurtis; Worrallo, Adam; Hartley, Thomas; Souleles, Nicos; Loizou, Michael (My University, 2017)
In this paper we present the design and development of a mobile application that assists learners of British Sign Language. The application uses interaction; namely, image recognition of a participant's gestures to give feedback as to the correctness of the gestures. Through designing with different algorithms and a user test, the efficacy of such an application is presented along with limitations that are present with current technology.
Keywords: Gesture recognition; Image recognition; Learning; Mobile application; Sign language